Impact of Mechanical Complications on Success of Dental Implant Treatments: A Case–Control Study - Ferreira, Patrícia W.; Nogueira, Paulo J.; Nobre, Miguel A. de Araújo; Guedes, Carlos Moura; Salvado, Francisco (European Journal of Dentistry, 2021)
Objective This study aimed to investigate the impact of mechanical complications on outcome measures for implant dentistry.Materials and Methods This case–control study included 282 patients with mechanical complications occurring in fixed prosthetic rehabilitation supported by immediate function implants with external connection (cases) and 282 individuals without mechanical complications (control). Pairing was performed for sex, age (range = 3 years), and follow-up months (range = 11 months). The primary outcome measure was implant survival, while the secondary outcome measures were marginal bone loss and biological complication parameters (peri-implant pathology, soft tissue inflammation, fistula formation, and abscess formation).Statistical Analysis Cumulative implant survival was estimated by using life tables. Descriptive statistics with 95% confidence intervals (CI) and inferential statistics (Chi-square test) were performed to evaluate differences between cases and controls. The significance level was set at 5%.Results The average follow-up duration was 8.5 years. Mechanical complications included prosthetic fracture (n = 159), abutment loosening (n = 89), prosthetic screw loosening (n = 20), milled abutment (n = 12), milled prosthetic screw (n = 1), and decemented crown (n = 1). Implant failure occurred in one patient from the control group, with survival rates of 100 and 99.6% for cases and controls, respectively (p = 0.317). The average marginal bone loss was 1.72 (95% confidence interval [CI]: 1.60–1.84) for cases and 1.55 (95% CI: 1.45–1.65) for controls (p = 0.068). Biological complications were observed in 90 patients, with significant differences between cases (n = 54) and controls (n = 36; p = 0.038).Conclusion Mechanical complications did not significantly influence survival or marginal bone loss; nevertheless, there is a need for studies with longer follow-up duration. Mechanical complications also significantly influence the incidence of biological complications.
Keywords: dental implants; complications; implant survival; bone loss